Japanese authorities’ policy toward the Jewish diaspora in Harbin (1931–1937) - Tianxiang, Meng (Journal of the Belarusian State University. International Relations, 2025)
After the 1917 October Revolution and the Russian Civil War, Russian Jews settled in Harbin, forming the Far East’s largest Jewish community by 1920. This article examines the difficult years of the Jewish diaspora in Harbin from 1931 to 1937, through some dimensions: identity of its status in Manchukuo, persecution by Russian fascists, and Japanese suppression of dissent. Drawing on archival sources and literature, it is shown that Japanese policy entailed systematic oppression, economic exploitation, and harsh repression, largely executed in collaboration with the antisemitic All-Russian fascist party.